2023
DOI: 10.3390/machines11060650
|View full text |Cite
|
Sign up to set email alerts
|

Attitude-Oriented Stability Control with Adaptive Impedance Control for a Wheeled Robotic System on Rough Terrain

Abstract: Base stability for a wheeled robot while driving over rough terrain is a challenging issue. This paper proposes a novel base-stability control framework, consisting of an AVIC (adaptive variable-impedance control), AVIC-based tracking controller, and a THV (terrain height variation) and AC (attitude control) AC-based controller to stabilize the base on rough terrain. The AVIC-based controller aims to track the desired trajectory of the robot base while suppressing lumped disturbance, including system uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Meanwhile, they carried out a simulation study on the obstacle-crossing ability of the mobile robot using Automatic Dynamic Analysis of Mechanical System (ADAMS) software. Xu et al (14) proposed a new stability control method of the chassis of a wheeled vehicle traveling on rough terrain to improve its attitude tracking performance. In addition, they verified the effectiveness and robustness of the proposed control method through a series of numerical tests, and found that the stability of the robot in motion is satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, they carried out a simulation study on the obstacle-crossing ability of the mobile robot using Automatic Dynamic Analysis of Mechanical System (ADAMS) software. Xu et al (14) proposed a new stability control method of the chassis of a wheeled vehicle traveling on rough terrain to improve its attitude tracking performance. In addition, they verified the effectiveness and robustness of the proposed control method through a series of numerical tests, and found that the stability of the robot in motion is satisfactory.…”
Section: Introductionmentioning
confidence: 99%